Implementation of Bin System Units for Efficient Harvest Transportation in the Palm Oil Agroindustry - Soesatrijo, Jojon (Fakultas Sains dan Teknologi Universitas Islam Negeri Sultan Syarif Kasim Riau, 2023)
This study aims to determine the effect and effectiveness of transporting fresh fruit bunches using the Bin System. This study method uses direct observation in the field regarding the Transportation of fresh fruit bunches from the collection point to the palm oil processing factory using the Bin System. Then carry out an analysis of the benefits obtained from transporting fresh fruit bunches using the Bin System, the time required to fill the bins, the number of fresh fruit bunches transported, the rate of fresh fruit bunches sent to the palm oil processing factory, and the total costs incurred for Transportation of fresh fruit bunches using Bin System per month.Based on the results of the studies that have been carried out, it appears that the time required to fill the bins is 81 minutes. The number of transporters is two people, the daily rate of fresh fruit bunches sent to the factory is six rates, and the total costs incurred for transporting fresh fruit bunches with Bin System in one month for Rp 23.985.222.